Perioperative dexmedetomidine effects on delirium in elderly patients after noncardiac surgery: A retrospective propensity score analysis - Wang, Hong-Wei; Chu, Qin-Jun; Zhu, Ze-Fei; Cheng, Ming; Li, Ze-Ping; Zang, Liang; He, Long; Chen, Lin-Na; He, Qian; Yang, Jian-Jun; Gu, Han-Wen (Frontiers in Pharmacology, 2025)
BackgroundDelirium is a complex syndrome with limited pharmacological treatment options, whereas non-pharmacological prevention strategies warrant further investigation. Dexmedetomidine, an α2-adrenergic receptor agonist commonly used for sedation and analgesia, has shown potential anti-inflammatory effects that may contribute to delirium prevention. We conducted a retrospective PSM analysis to evaluate the effectiveness of dexmedetomidine in preventing postoperative delirium in elderly ICU patients undergoing noncardiac surgery.MethodsA retrospective analysis was conducted, including patients undergoing noncardiac surgeries after surgery. The main outcome was the 7-day incidence of delirium. Secondary outcomes included the length of hospital stay, postoperative nausea and vomiting, and postoperative complications. Propensity score matching and regression models were utilized to adjust for confounders and to investigate associations between the use of dexmedetomidine and outcomes.ResultsA total of 19,899 patients were included, and 3,169 pairs were matched after propensity score matching. After matching, the incidence of postoperative delirium was 8.68% in the cohort with perioperative dexmedetomidine (test group) and 17.80% in the cohort without dexmedetomidine (control group), p < 0.001. The numerical rating scale in the test group was significantly decreased (mean ± SD, 2.4 ± 0.9 vs. 2.6 ± 0.8, p < 0.001). Hypotension (14.86% vs. 14.04%, p < 0.001) was increased, whereas hypertension (10.67% vs. 13.13%, p < 0.001) and tachycardia (16.81% vs. 10.71%, p < 0.001) were decreased in the test group.ConclusionPerioperative infusion of dexmedetomidine may reduce the incidence of delirium in elderly patients after noncardiac surgery.